Fibroblast Growth Factor Receptor Functions in Glioblastoma - Jimenez-Pascual, Ana; A. Siebzehnrubl, Florian (Cells (Basel, Switzerland), 2019)
Glioblastoma is the most lethal brain cancer in adults, with no known cure. This cancer is characterized by a pronounced genetic heterogeneity, but aberrant activation of receptor tyrosine kinase signaling is among the most frequent molecular alterations in glioblastoma. Somatic mutations of fibroblast growth factor receptors (FGFRs) are rare in these cancers, but many studies have documented that signaling through FGFRs impacts glioblastoma progression and patient survival. Small-molecule inhibitors of FGFR tyrosine kinases are currently being trialed, underlining the therapeutic potential of blocking this signaling pathway. Nevertheless, a comprehensive overview of the state of the art of the literature on FGFRs in glioblastoma is lacking. Here, we review the evidence for the biological functions of FGFRs in glioblastoma, as well as pharmacological approaches to targeting these receptors.